2015
DOI: 10.1186/s40508-015-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of stability of a lipase by subjecting to three phase partitioning (TPP): structures of native and TPP-treated lipase from Thermomyces lanuginosa

Abstract: Background:The lipase enzyme converts long chain acyltriglycerides into di-and monoglycerides, glycerol and fatty acids. The catalytic site in lipase is situated deep inside the molecule. It is connected through a tunnel to the surface of the molecule. In the unbound state under aqueous conditions, the tunnel remains closed. The tunnel can be opened when the enzyme is exposed to a lipid bilayer or a detergent or many hydrophobic/hydrophilic surfaces. Results:In the present study, the lipase was subjected to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…With an increase in the length of lipase substrate molecules, the efficiency of biocatalysis decreased. The broader specificity of the immobilized lipase towards the alcohol substrate indicated that the S 2 -binding site of the active site of the lipase was wider in size than the S 1 -binding site, which allowed us to confirm the conclusions about the structure of the active site of the T. lanuginosus lipase made in [27,[30][31][32][33]: the active site of the RML type lipase, to which TLL belongs, is located close to the surface of the enzyme globule and has a narrow gap for S 1 (acid), and a wider one for S 2 (alcohol).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…With an increase in the length of lipase substrate molecules, the efficiency of biocatalysis decreased. The broader specificity of the immobilized lipase towards the alcohol substrate indicated that the S 2 -binding site of the active site of the lipase was wider in size than the S 1 -binding site, which allowed us to confirm the conclusions about the structure of the active site of the T. lanuginosus lipase made in [27,[30][31][32][33]: the active site of the RML type lipase, to which TLL belongs, is located close to the surface of the enzyme globule and has a narrow gap for S 1 (acid), and a wider one for S 2 (alcohol).…”
Section: Resultssupporting
confidence: 75%
“…The crystal structure of TLL with a resolution of 2.3 Å was taken from the PDB database (PDB ID: 4ZGB). For simulation, a form of lipase in which the active site was in the closed conformation, was used [27]. CNT structures of various sizes were generated using the Nanotube Modeler program and optimized using Avogadro.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the flexibility of the protein, B-factors of the Cα atoms in TLL were extracted from the crystal structure file (PDB ID: 4ZGB and 1DT3) [42,43]. The B-factor values of each atom were normalized to have a distribution of zero mean and unit variance based on the following equation:…”
Section: Prediction Of the Mutagenesis Sites Via B-factor Comparisonmentioning
confidence: 99%
“…Early studies on lid motion mainly focused on the fungal lipase family, particularly the triacylglycerol lipase family (called the RmL lipase family), such as Rhizomucor miehei lipase (RML) (Moroz et al., 2019). According to the configurations of lipase lid, the typical lid motion was assumed to follow a two‐step opening mechanism that first gives rise to a semi‐open conformation upon adsorption at the interface, followed by a full opening of the lid upon substrate binding (Kumar et al., 2015; Longhi et al., 2011) (Figure 4). Hinge‐type motion is similar to rotations around an articulated joint that allows major conformational changes without altering the internal packing of the individual domains (Papaleo et al., 2016).…”
Section: Dynamic Behaviors Of the Lidmentioning
confidence: 99%